2021
DOI: 10.1111/ijcp.14628
|View full text |Cite
|
Sign up to set email alerts
|

Optical coherence tomography in peripheral arterial disease: A systematic review

Abstract: Optical coherence tomography (OCT) is an imaging technique analogous to ultrasound, using light instead of sound waves. 1 It utilises interferometry to map the reflectivity of light in terms of depth to provide high-resolution, cross-sectional images of the internal tissues. 2 Upon its first realisation by Huang et al for imaging of the retina and the coronary arteries in 1991, 3 it was initially utilised in the field of ophthalmology. 4,5 Owing to its high resolution of images, it was subsequently applied in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Optical coherence tomography (OCT) represents a valuable imaging modality in the percutaneous intervention of the coronary arteries, guiding stent implantation and studying mechanisms of stent failure 1 . Prior studies suggested the feasibility of OCT in peripheral artery disease, 2 although its usefulness in the percutaneous intervention of the splanchnic arteries has not been well defined. Hereby, we present a case of stent failure of the terminal branch of the superior mesenteric artery (SMA) studied by OCT imaging.…”
mentioning
confidence: 99%
“…Optical coherence tomography (OCT) represents a valuable imaging modality in the percutaneous intervention of the coronary arteries, guiding stent implantation and studying mechanisms of stent failure 1 . Prior studies suggested the feasibility of OCT in peripheral artery disease, 2 although its usefulness in the percutaneous intervention of the splanchnic arteries has not been well defined. Hereby, we present a case of stent failure of the terminal branch of the superior mesenteric artery (SMA) studied by OCT imaging.…”
mentioning
confidence: 99%